Framework To Guide The Collection And Use Of Patient-Reported Outcome Measures In The Learning Healthcare System. Issue 1 (4th September 2017) - Franklin, Patricia; Chenok, Kate; Lavalee, Danielle; Love, Rebecca; Paxton, Liz; Segal, Courtney; Holve, Erin
Background: Web-based collection of patient-reported outcome measures (PROMs) in clinical practice is expanding rapidly as electronic health records include web portals for patients to report standardized assessments of their symptoms. As the value of PROMs in patient care expands, a framework to guide the implementation planning, collection, and use of PROs to serve multiple goals and stakeholders is needed. Methods: We identified diverse clinical, quality, and research settings where PROMs have been successfully integrated into care and routinely collected and analyzed drivers of successful implementation. Findings are based on key informant interviews with 46 individuals representing 38 organizations, of whom 40 participated in a webinars series, and 25 attended an in-person workshop designed to enable broad stakeholder input, review and refinement of the proposed PROMs implementation model. Stakeholders identified differing uses of PROMs to support: 1) individual patient care decisions, 2) quality improvement initiatives, 3) payer mandates, and 4) population health and research. Results: The implementation framework and steps that are consistently identified by stakeholders as best practices to guide PROM capture and use are described. Of note, participants indicate that web-based informatics tools are necessary but not sufficient for PROM use, suggesting that successful PROM implementation requires integration into clinic operations and careful planning for user's analytic needs. Each of the four identified uses may require implementation modifications at each step to assure optimal use. Conclusions: The proposed framework will guide future PROM implementation efforts across learning health care systems to assure that complete PROMs are captured at the correct time, and with associated risk factors, to generate meaningful information to serve diverse stakeholders.